2001
DOI: 10.1002/ab.4
|View full text |Cite
|
Sign up to set email alerts
|

Reduced right hemisphere activation in severely abused violent offenders during a working memory task: An fMRI study

Abstract: This study uses functional magnetic resonance imaging (fMRI) to address two important gaps in our knowledge of brain functioning and violence: (1) What are the brain correlates of adults in the community who have suffered severe physical abuse early in life and who go on to perpetrate serious violence in adulthood? (2) What characterizes those who experience severe physical abuse but who refrain from serious violence? Four groups of participants recruited from the community (controls, severe physical child abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 66 publications
3
49
0
2
Order By: Relevance
“…Alternatively, Birbaumer and colleagues (2005) revealed that criminal psychopaths showed no significant differential activation in the limbic-prefrontal circuit (amygdala, orbitofrontal cortex, insula, and anterior cingulate cortex), which was activated in healthy controls during an aversive conditioning task. Using a visual/ verbal working memory task, Raine et al (2001) showed significant reduced activation in the right hemisphere, particularly in the temporal cortex, in violent offenders with a history of abuse compared with controls. Again, using a working memory task, activation deficits in the left frontal gyrus and anterior cingulate cortex were found in violent APD patients compared with normal controls (Kumari et al, 2006).…”
Section: Fmri Findings In Antisocial Individualsmentioning
confidence: 98%
See 1 more Smart Citation
“…Alternatively, Birbaumer and colleagues (2005) revealed that criminal psychopaths showed no significant differential activation in the limbic-prefrontal circuit (amygdala, orbitofrontal cortex, insula, and anterior cingulate cortex), which was activated in healthy controls during an aversive conditioning task. Using a visual/ verbal working memory task, Raine et al (2001) showed significant reduced activation in the right hemisphere, particularly in the temporal cortex, in violent offenders with a history of abuse compared with controls. Again, using a working memory task, activation deficits in the left frontal gyrus and anterior cingulate cortex were found in violent APD patients compared with normal controls (Kumari et al, 2006).…”
Section: Fmri Findings In Antisocial Individualsmentioning
confidence: 98%
“…Raine et al (2001) Violent offenders Working memory task. A sequence of familiar objects was presented on the screen and the participants were asked to press a button when a previously seen object was presented.…”
Section: Pet Findings In Antisocial Individualsmentioning
confidence: 99%
“…A number of investigations have demonstrated associations between childhood maltreatment and poorer cognitive functioning in adulthood, including reduced intellectual and academic functioning (Perez and Widom, 1994), defi cits on tasks of verbal learning and memory (Bremner et al, 1995), working memory (Raine et al, 2001), and executive control (Mezzacappa et al, 2001), impaired eye-tracking (Irwin et al, 1999), and a higher rate of neurological soft signs (Gurvits et al, 2000). Fewer investigations have examined the relationship between maltreatment during childhood and neurocognitive functioning in schizophrenia spectrum disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conclusions on temporal lobe were not consistent. Some studies have reported that temporal lobe functioning was reduced in aggressive patients [23]. However, some studies have reported the opposite conclusion.…”
Section: Discussionmentioning
confidence: 96%